The relationship between extra-curricular activities and learning creativity of junior high school students - Sijabat, Masdiana (Trigin Institute, 2023)
Extra-curricular activities are one way to achieve institutional goals. These activities are carried out outside of school hours and are generally in the form of assignments, completed through experiments or in the form of exercises as practice and theory received at school. When students carry out extra-curricular activities, it means that they are practicing their learning creativity. With the habit of students practicing their lessons from school, the more creative potential they have will develop. So extra-curricular activities in addition to achieving institutional goals, students are also highly expected to be independent after graduating from school. However, there are still many teachers who do not realize the great benefits of extra-curricular activities so that they are not serious about implementing them. In this study, the authors determined the population of class VII of Gajah Mada Binjai Private Junior High School for the 2023/2024 Learning Year, which randomly took 82 students as respondents. The method used is descriptive method, to obtain data the researcher uses a closed questionnaire and this questionnaire is divided into two, namely the first part to obtain data about extra-curricular activities and the second part to obtain data about student learning creativity. Respondents' answers were given a value with the following weights: option a value 4, option b value 3, option c value 2, option d value 1. The data is quantitative and the analysis technique is statistical analysis of correlation using the Product Moment Statistical formula developed by Pearson, namely: = . Hypothesis testing is based on a 5% significance level or using a 95% confidence level using the r table (correlation table) with a sample size of 82. Then from the calculation results obtained r = 0.9977 and r correlation table = 0.217, which means high correlation. Thus it can be concluded that extra-curricular activities have a positive and convincing relationship with the learning creativity of seventh grade students at Gajah Mada Binjai Private Junior High School for the 2023/2024.